If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying M + 2 + 5 = 10 Reorder the terms: 2 + 5 + M = 10 Combine like terms: 2 + 5 = 7 7 + M = 10 Solving 7 + M = 10 Solving for variable 'M'. Move all terms containing M to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + M = 10 + -7 Combine like terms: 7 + -7 = 0 0 + M = 10 + -7 M = 10 + -7 Combine like terms: 10 + -7 = 3 M = 3 Simplifying M = 3
| -8*0= | | 0.06x=0.03 | | 4h-7=-31 | | 12x+y=22 | | 2(x+3)-5(x+1)=23 | | 14-(0.5*p)=(0.25*p)-1 | | 8x-6y+1= | | b=7/6(j-27) | | 5x^4-4x^3+3x^2-1=0 | | (-1/6)(x-12)+(1/3)(x+3)=x+3 | | n*6=70 | | 8e-9=-2 | | 1/5x=-4 | | -7(x+4)+15x=8(x+2)+15 | | 1=4-2h | | 10b-3b=14 | | 3w^2-400w+10000=0 | | -31=5+9a | | 34(x-136)=68 | | 4y+7=-6+5y | | 3(2x-4)-5x=2 | | 2c-2=-5 | | 2r+7=23 | | 3a-5=2(a+1)+8a+2 | | 8(3x-1)=2(12x+6) | | 19x-18=77 | | 320+80t=7208-220t | | x-4/5=11/7 | | 4+13s-1=7s+69-5s | | 6x+14=116-7 | | 10r+7=51 | | 5(2x^2)-3x-22=0 |